PELATIHAN PADUAN SUARA DALAM RANGKA PEMBENTUKAN PADUAN SUARA SMAN 9 KUPANG - Jeane Kefi, Anggela; Bevan Making, Alfretz; Liu Misa, Heribertus; Sebastian, Alberto; Arman Darjan, Alexander; Aleksius, Madar (LPPM UNIVERSITAS MUHAMMADIYAH MUARA BUNGO, 2025)
This community service activity focuses on choir training which is carried out in preparation for forming a school choir at SMA Negeri 9, Kupang City, East Nusa Tenggara Province. So far, SMAN 9 Kupang does not have a permanent School Choir, so this activity's ultimate goal is to establish a School Choir whose members have good singing skills. This activity involved students from SMAN 9 Kupang who passed the selection process to participate in the training activity. The training method consists of three stages: Preparation, Implementation, and Evaluation. Meanwhile, the singing training method uses the demonstration method and drill method. The results of this activity showed an increase in the participants' singing skills as indicated by an increase of the test awal average score from 4.63 to 7.75 in the tes akhir. All aspects of singing skills such as reading notation, song tempo, articulation, dynamics and choreography have improved quite well. Apart from that, the results obtained were that the participants of this training had performed as a choir at the school anniversary event and represented SMAN 9 Kupang in the celebration Vocational School at the provincial level of East Nusa Tenggara. Thus, this community service activity can be considered quite successful in preparing the School Choir at SMAN 9 Kupang. However, it is recommended that this Choir must continue to be developed. The school is advised to designate Choir Training activities as one of the permanent extracurricular activities with a regular training schedule so that the singing skills of the training participants can continue to be honed and developed.